A word from our Editor-in-Chief: PROSPECTS OF NONCONVENTIONAL TECHNOLOGIES (Nonconventional Technologies Review, 2017)
14 years after the publication of the first "Nonconventional Technology Treaty", it is necessary to reconsider the issue, which is so complex and important for the future of developing performing technologies. It is noted that there are no radical changes at the level of their approach.The paper is the result of an analysis of news and perspective aspects of the technologies, in general, on the role and importance of unconventional technologies in the future.In the industrial environment, the machines are still stronger, with higher reliability, capable of working under forced conditions, with active elements actuated by shocks, high pressures or extreme temperature conditions.